2018
DOI: 10.1038/s41598-018-19316-y
|View full text |Cite
|
Sign up to set email alerts
|

Collagen-Binding Hepatocyte Growth Factor (HGF) alone or with a Gelatin- furfurylamine Hydrogel Enhances Functional Recovery in Mice after Spinal Cord Injury

Abstract: The treatment of spinal cord injury (SCI) is currently a significant challenge. Hepatocyte growth factor (HGF) is a multipotent neurotrophic and neuroregenerative factor that can be beneficial for the treatment of SCI. However, immobilized HGF targeted to extracellular matrix may be more effective than diffusible, unmodified HGF. In this study, we evaluated the neurorestorative effects of an engineered HGF with a collagen biding domain (CBD-HGF). CBD-HGF remained in the spinal cord for 7 days after a single ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…In another study, CBD-fused FGF-2 showed the ability to induce significantly higher mesenchymal cell proliferation and callus formation in a mice fracture model compared to wild-type FGF-2 (Sekiguchi et al, 2018). Similarly, a CBD-fused hepatocyte growth factor (HGF) delivered via hydrogel improved recovery after spinal cord injury in mice compared to wild-type HGF (Yamane et al, 2018).…”
Section: Engineering Gfs For Non-covalent Interaction To Biomaterialsmentioning
confidence: 99%
“…In another study, CBD-fused FGF-2 showed the ability to induce significantly higher mesenchymal cell proliferation and callus formation in a mice fracture model compared to wild-type FGF-2 (Sekiguchi et al, 2018). Similarly, a CBD-fused hepatocyte growth factor (HGF) delivered via hydrogel improved recovery after spinal cord injury in mice compared to wild-type HGF (Yamane et al, 2018).…”
Section: Engineering Gfs For Non-covalent Interaction To Biomaterialsmentioning
confidence: 99%
“…HGF also inhibits the infiltration of neutrophils through the down-regulation of adhesion molecules [23]. Our previous report demonstrated that the infiltration of macrophages and neutrophils was reduced under the influence of HGF in the acute phase of SCI [7]. The anti-inflammatory activities of HGF contribute to reduce secondary damage and improve functional recovery after SCI.…”
Section: Neurotrophic Activities Of Hgf In Scimentioning
confidence: 99%
“…Optimization of the routes of drug administration is essential to increase drug efficacy and address clinical medicines. Previous in vivo animal studies tackling the subject of SCI treatment evaluated different HGF therapy approaches, such as the use of recombinant HGF [9], viral vectors [6], grafting of mesenchymal stem cells that over-express HGF [8], or utilization of engineered HGF with a collagen biding domain (CBD-HGF) [7]. Irrespective of the therapeutic approach, local administration of HGF is required as the endogenous HGF supply is limited in the acute phase of SCI.…”
Section: Recent Advances Towards Clinical Applications In Sci Recomentioning
confidence: 99%
See 2 more Smart Citations